Saliva alcohol concentrations in accident and emergency attendances. Issue 4 (1st July 2001) - Simpson, T; Murphy, N; Peck, D F
Abstract : Objectives —Although alcohol is known to play a key part in accidents, no UK study has assessed alcohol concentrations in a comprehensive sample of accident and emergency (A&E) attenders. This study set out to do this, and examine the relation between alcohol concentrations and the severity, type and circumstances of presentation, and the sociodemographic characteristics of patients. Methods —A survey was conducted of all new A&E attenders (aged 10 years or over). Two 24 hour periods for each day of the week were covered in 6, 7 or 11 hour sessions over a two month period. Alcohol concentrations were assessed from saliva samples using a disposable device. Data were collected from 638 attenders, of whom 544 provided saliva samples; the remainder refused or were unable to participate. Results —Positive saliva alcohol readings were obtained in 22% of attenders (95%CI 19% to 26%); this increased to 25% if others were included (for example, those who refused to participate but were judged to be intoxicated). Alcohol was associated with 94% of incidents of self harm, 54% of non-specific/multiple complaints, 47% of collapses, 50% of assaults, and 50% of patients admitted to hospital. Higher concentrations of alcohol were found from Friday to Sunday, between midnight and 0900, and in patients aged 41 to 60. Among people with positive alcohol results, those attending with a companion had higher concentrations than those attending alone. There were no significant differences between men and women in alcohol concentrations. Discussion —These findings show that alcohol use is an important factor in A&E attendance, but it should not be assumed that there is a causal relation between alcohol use and injury. Several accident related and sociodemographic variables were predictive of alcohol use before attending. The overall level of prediction was too weak to permit accurate identification of drinkers for screening purposes, but routine alcohol concentration assessments may be justified in the high risk groups identified in this study. A&E departments may be convenient and fruitful settings for brief interventions with early problem drinkers.